Addressing the Temporal Constraint in Sagittal Synostosis: Modification of the Extended Suturectomy Technique. Issue 2 (June 2022) - Kurnik, Nicole M.; Pflibsen, Lacey R.; Howarth, Ashley L.; Walton, Mollie M.; Bristol, Ruth E.; Beals, Stephen P.; Shafron, David H.; Singh, Davinder J.
Introduction: Numerous surgical techniques have been described for correction of sagittal synostosis. However, many do not address the often-persistent temporal constraint. To address the deformity, the endoscopic surgical technique used at this institution was modified to include frontal bone releasing osteotomies across the coronal sutures in the area of the temporal constraint. The purpose of this study was to evaluate the early benefit of this technique. Methods: A retrospective review of electronic health records was performed for 31 consecutive patients who received frontal bone releasing osteotomies and 33 consecutive patients before frontal bone releasing osteotomies were initiated in May of 2015. Both cohorts were age matched and underwent the same postsurgical orthotic therapy protocol. The Whitaker classification system and a visual analog scale were used to evaluate for temporal constraint. Images were reviewed at 6 months after the postsurgical orthotic was removed. Results: Patients who received frontal bone releasing osteotomies had significantly improved Whitaker grade scores (1.27 vs 1.64, P  < .05) and greater improvement in visual analog scores (39.97 vs 25.64, P  < .05) compared with those who did not. Both ratings showed good interrater reliability. Conclusions: During the early postsurgical period, greater and more rapid improvement in the temporal constraint was seen in the group of patients who had additional frontal bone releasing osteotomies during the correction of sagittal synostosis. Longer-term follow-up is needed to evaluate maintenance of the improvement as relapse and poor growth in this area are known to occur.